Stabilization of Aragonite: Role of Mg2+ and Other Impurity Ions - Boon, Matthew; Rickard, William; Rohl, Andrew; Jones, Franca (AMER CHEMICAL SOC, 2020)
Copyright © 2020 American Chemical Society. Aragonite formation and stabilization in seawater is still an area of active investigation since the thermodynamically stable product at room temperature is calcite. In this manuscript, purely inorganic systems that were found to stabilize aragonite were analyzed by various techniques. Dynamic light scattering was used to characterize the nucleation behavior of the system, and it was found that the presence of magnesium ions during crystal formation inhibits nucleation overall, not just calcite nucleation. In addition, it was found that sulfate is not necessary to stabilize aragonite. Microanalysis by energy dispersive X-ray spectroscopy and electron backscatter diffraction revealed that the aragonite that was formed had a disordered core with sodium, magnesium, and sulfate ions incorporated into the structure. To the best of the authors' knowledge this is the first time an amorphous calcium carbonate (ACC) core in aragonite has been visualized in a completely abiotic, synthetic system (i.e., in the absence of organic molecules). Inclusion of these impurities into the structure may explain the stability of aragonite in natural seawaters.